Anxiety in response to the climate and environmental crises: validation of the Hogg Eco-Anxiety Scale in Germany - Heinzel, Stephan; Tschorn, Mira; Schulte-Hutner, Michael; Schäfer, Fabian; Reese, Gerhard; Pohle, Carina; Peter, Felix; Neuber, Michael; Liu, Shuyan; Keller, Jan; Eichinger, Michael; Bechtoldt, Myriam (Frontiers in Psychology, 2023)
Background: As the climate and environmental crises unfold, eco-anxiety, defined as anxiety about the crises’ devastating consequences for life on earth, affects mental health worldwide. Despite its importance, research on eco-anxiety is currently limited by a lack of validated assessment instruments available in different languages. Recently, Hogg and colleagues proposed a multidimensional approach to assess eco-anxiety. Here, we aim to translate the original English Hogg Eco-Anxiety Scale (HEAS) into German and to assess its reliability and validity in a German sample. Method: Following the TRAPD (translation, review, adjudication, pre-test, documentation) approach, we translated the original English scale into German. In total, 486 participants completed the German HEAS. We used Bayesian confirmatory factor analysis (CFA) to assess whether the four-factorial model of the original English version could be replicated in the German sample. Furthermore, associations with a variety of emotional reactions towards the climate crisis, general depression, anxiety, and stress were investigated. Results: The German HEAS was internally consistent (Cronbach’s alphas .71 - .86) and the Bayesian CFA showed that model fit was best for the four-factorial model, comparable to the factorial structure of the original English scale (affective symptoms, rumination, behavioral symptoms, anxiety about personal impact). Weak to moderate associations were found with negative emotional reactions to the climate crisis and with general depression, anxiety and stress. Discussion: Our results support the original four-factorial model of the scale and indicate that the German HEAS is a reliable and valid scale to assess eco-anxiety in German speaking populations.